1992
DOI: 10.1111/j.1600-051x.1992.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐speed filming of the Periotest measurement

Abstract: Periodontal disease may be diagnosed with the Periotest technique, which involves electronically controlled and reproducible percussion of tooth. The movement on percussion was investigated with high-speed film and then compared with the return of teeth after static deflection for several seconds as has been reported previously by Lukas and Scholz. The elastic and viscous properties of the periodontium and the surrounding bony tooth socket are to a large extent non-linear. The 10-20 microns deflection of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This is in agreement with many studies. [ 37 71 72 73 ] Söder et al . found that PI was significantly correlated with halitosis and that periodontitis patients with halitosis had more severe disease than those without.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with many studies. [ 37 71 72 73 ] Söder et al . found that PI was significantly correlated with halitosis and that periodontitis patients with halitosis had more severe disease than those without.…”
Section: Discussionmentioning
confidence: 99%
“…Methods for measuring tooth mobility include the evaluation of tooth movement under application of a defined load (24, 28, 29), use of the Mühlemann periodontometer (14), and use of the Periotest device (15, 17, 19, 25). The Periotest method is a well established and accepted technique for measuring tooth mobility in both periodontology (30–34) and dental traumatology (15, 17, 19, 25, 35–37). The advantages of this method are easy application, the ability to measure both horizontal and vertical dimension, and highly reproducible results (14).…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the sutures used to close the interdental papilla on top of the barrier membrane, the socalled "offset suture," that finds its vestibular anchorage at the level of the buccal keratinized tissue of the tooth next to the experimental tooth. Tooth mobility was evaluated as damping characteristics of the periodontal ligament using a purpose-built electronic device as previously described [37][38][39] and expressed as conventional units (PTU).…”
Section: Clinical Measurementsmentioning
confidence: 99%